2017
DOI: 10.1111/jpc.13710
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial anomalies and mothers’ psychological functioning: The mediating role of social support

Abstract: Mothers of children with CFAs may experience increased psychological distress in comparison with the general population. Increased social support may reduce the risk of psychological distress, thus enhancing quality of life among such mothers. The majority of mothers of children with CFAs in Australia may not be routinely offered psychological support services in spite of their elevated psychological risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Parents of children with health needs often have to take on a variety of roles, such as being caregivers, advocates, and care coordinators (Feragen et al, 2020). Parent/caregivers have been shown to experience higher levels of parenting stress (Case et al, 2018, Cousino and Hazen, 2013) that can impact upon the psychological adjustment of the whole family (Cousino and Hazen, 2013). Past studies have found that parents of children diagnosed with AS report increased levels of parenting stress attributed to difficulties accepting their child's condition, their child's behavior, and parental low self-esteem (Sarimski, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Parents of children with health needs often have to take on a variety of roles, such as being caregivers, advocates, and care coordinators (Feragen et al, 2020). Parent/caregivers have been shown to experience higher levels of parenting stress (Case et al, 2018, Cousino and Hazen, 2013) that can impact upon the psychological adjustment of the whole family (Cousino and Hazen, 2013). Past studies have found that parents of children diagnosed with AS report increased levels of parenting stress attributed to difficulties accepting their child's condition, their child's behavior, and parental low self-esteem (Sarimski, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been more attention given to patient and parental proxy reported measures of quality of life (QoL) (Nelson et al, 2012; Stock & Feragen, 2016; Case et al, 2018). There are a growing number of studies investigating QoL both in children with OFC and more generally in children with facial deformities, including 2 systematic reviews (Klassen et al, 2012; Tapia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%